AKURASI ESTIMASI PRODUKSI PADI DENGAN METODE NDVI BERDASARKAN SENTINEL-2 DI KABUPATEN TANAH LAUT KALIMANTAN SELATAN - Rahmadi, Abdul Holid; Wahdah, Raihani; Razie, Fakhrur; Susanti, Hilda (EnviroScienteae, 2024)
Remote sensing is a technology that is very useful in every step of the planning process and has been used in developed countries and several regions in developing countries. The aim of this research is to interpret rice production in Tanah Laut Regency using the NDVI method based on Sentinel-2 and determine the accuracy of rice production estimates in Tanah Laut Regency using the NDVI method based on Sentinel-2. Research methods include preparation, measurement principles, data collection, radiometric correction, geometric correction, creating a vegetation index, determining the best vegetation index, estimating rice production, accuracy testing, image analysis, and rice production potential. The result of this research is a rice production estimation model of y = 0.341 + 4.319 NDVI. The NDVI estimation results in Tanah Laut Regency range from 1.36 t ha-1 to 3.36 t ha-1 with an average production of 2.67 t ha-1. The results of the analysis show that there is no real difference at the 95% confidence level between the results of the NDVI estimation of rice production using Sentinel-2 imagery and the results of the field survey of rice production based on a coefficient of determination (R2) of 0.749 and a standard error (SE) of 0.29 t ha-1.